Selection of alternative solution for implementing green productivity of milk agroindustry in Malang Raya - Andan Linggar Rucitra; Ardaneswari Dyah Pitaloka Citraresmi; Widhistya Kartikaningrum (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
The dairy agroindustry in Malang Raya has high development potential due to the increasing market demand for dairy products. Previous studies have analyzed the application of green productivity at SMEs Milk X in Malang City and proposed alternative solutions to make liquid organic fertilizers, install wastewater treatment equipment, and utilize wastewater as hydroponic growing media. This study aimed to follow up the results of previous studies, focusing on selecting alternative solutions to be applied to SMEs Milk X and analyze the green productivity index (GPI) value from the selected alternative solutions. In selecting alternatives, the analytical hierarchy process (AHP) method was used with data obtained from questionnaires. The results obtained indicate that the selected alternative solution that potentially to be applied in the SMEs Milk X was the manufacture of liquid organic fertilizer. In this alternative, the GPI value increased from 0.24 to 1.078.